Analisis Penerapan Kurikulum Merdeka Terhadap Kecerdasan Interpersonal Siswa Sekolah Dasar - Joni Albar; Mastiah Mastiah (STKIP Melawi, 2022)
Abstract: Optimizing the independent curriculum in improving the quality of education with the concept of simplification and deepening of material and strengthening the profile of Pancasila students. The purpose of this study is to analyze the application of the independent curriculum to the interpersonal skills of elementary students. This study uses a literature review method on 15 articles published in the last 10 years. Data sources are scientific journals in the Google Scholar database and other relevant journal sites. Techniques of data analysis were analyzing, describing, concluding, and describing. The results of this research show that there is the effects of student interpersonal intelligence that caused by various indicators that support the excess of an independent curriculum, which has a significant impact on efforts to improve the quality of education by updating the curriculum. This study concludes that the application of an independent curriculum by optimizing the ability of teachers in the learning process can have a significant impact on the concept of independent learning and that simplification of objectives and student-centered learning processes can improve students' interpersonal intelligence. Keywords: Independent Curriculum, Interpersonal Intelligence Abstrak: Optimalisasi kirikulum merdeka didalam memperbaiki kulitas pendidikan dengan konsep pemyederhanaan serta pendalaman materi dan penguatan terhadap profil pelajar Pancasila. Tujuan Penelitian ini adalah menganalisis penerapan kurikulum merdeka terhadap kemampuan interpersonal siswa sekolah dasar. Penelitian ini menggunakan sebuah metode literature review terhadap 15 artikel 10 tahun terakhir. Sumber data, yaitu jurnal ilmiah dalam database Google Scholar dan situs jurnal lainnya yang relevan. Teknik analisis data dengan menganalisis, mendeskripsikan, menyimpulkan dan deskripsi. Hasil yang didapatkan terdapat Pengaruh Kecerdasan Interpersonal Siswa yang disebabkan oleh berbagai indikator-indikator yang mendukung dari kelebihan kurikulum merdeka yang memberikan dampak signifikan upaya perbaikan kualitas pendidikan dengan pemutakhiran kurikulum. Kesimpulan dari penelitian ini bahwa penerapan kurikulum merdeka dengan mengoptimalkan kemampuan guru di dalam proses pembelajaran mampu memberikan dampak yang siqnifikan dengan konsep pembelajaran merdeka dan penyederhanaan tujuan dan proses pembelajaran yang berpusat pada siswa mampu meningkatkan kecerdasan interpersonal siswa. Kata Kunci: Kurikulum Merdeka, Kecerdasan Interpersonal